Awareness and practices regarding standard precautions for infection control among the hospital support staff in a tertiary care hospital in South India: a cross sectional study - Jha, Anusha Taarinie; Jacob, George P.; Ramireddy, Mahathi; K., Yogesh Kini (International Journal Of Community Medicine And Public Health, 2017)
Background: Compliance with standard precautions reduces the risk of exposure to blood and body fluids. The awareness regarding infection control and appropriate practices among hospital support staff is critical to prevent HAIs. Hence this study was conducted with the objectives of evaluating the awareness regarding standard precautions for infection control among hospital support staff and to identify the barriers, if any, to comply with standard infection control protocol among them. Methods: A cross-sectional study was conducted in a tertiary care hospital after obtaining the necessary ethical clearance and required permissions. Sample size was calculated to be 80. Written informed consent was taken from the participants. A questionnaire in the local language was used to collect the data. The statistical analysis was done using SPSS version 15. The results were expressed as proportions. Chi-square test was applied to study the association. Results: 81 workers participated in the study. 91.4% knew that hand washing is the most effective way to prevent health care associated infections. 75.3% were aware about categories of wastes. Among 59 staff who were liable to come in contact, 57 (96.6%) used protective barriers while serving HIV/TB patients. 51.9% of the participants were vaccinated against Hepatitis B infection. Conclusions: The awareness and practices of the hospital support staff regarding standard precaution for prevention of infection was inadequate.